Answer:
12:1
Step-by-step explanation:
12:1Answer:
Step-by-step explanation:
Given that f(x) = x2 – 7x – 1, g(x) = 2x – 3, and h(x) = 4x – 5 find each function.
(f + g)(x)
options:
A) x2 – 5x – 4
B) x2 – 11x + 4
C) x2 – 3x – 6
D) x2 – 5x – 6
Answer:
A)
Step-by-step explanation:
(f+g)(x) = f(x) + g(x)
now plug in the expressions of f(x) and g(x) :
(f+g)(x) = [tex]x^{2} -7x-1 + 2x-3[/tex]
we combine like terms we get :
(f+g)(x) = [tex]x^{2} -7x+2x -1-3[/tex]
we simplify we get :
(f+g)(x)=[tex]x^{2} -5x-4[/tex]
so the answer is A)
Answer:a
Step-by-step explanation:
Which represents a perfect cube?
Which table represents an arithmetic sequence?
Answer:
The third table is an arithmetic sequence . Its difference is -1.4.
Step-by-step explanation:
In an arithmetic sequence the difference between one term and the next is a constant
8.7 - 1.4 = 7.3
7.3 - 1.4 = 5.9
5.9 - 1.4 = 4.5
4.5 - 1.4 = 3.1
Answer:3rd table
Step-by-step explanation:
Find the length of the segment indicated.
Answer: The length of the indicated segment is 14.45 units.
Step-by-step explanation: We are given to find the length of the indicated segment.
From the figure, we note that
A chord is bisected by the radius of the circle that makes a right-angled triangle with hypotenuse measuring 16.1 units and the other two sides measures x units and 7.1 units.
Using Pythagoras theorem, we get
[tex]x^2+7.1^2=16.1^2\\\\\Rightarrow x^2+50.41=259.21\\\\\Rightarrow x^2=259.21-50.41\\\\\Rightarrow x^2=208.8\\\\\Rightarrow x=\pm\sqrt{208.8}\\\\\Rightarrow x=\pm14.45.[/tex]
Since x is the length of side of a triangle, so we get
x = 14.45.
Thus, the length of the indicated segment is 14.45 units.
Which values of a,b and c represent the answer in simplest form
[tex]1 \frac{3}{4}[/tex]
Fractional division is fractional multiplication with the second fraction the reciprocal of itself. This means the problem can be written as [tex]\frac{7}{9}*\frac{9}{4}[/tex]. Fractional multiplication results in the multiplication of the numerators and denominators---in this case, [tex]\frac{7}{4}=1\frac{3}{4}[/tex]
Answer:
Option B) a = 1, b = 3, c = 4
Step-by-step explanation:
We are given the following information in the question:
We are given an expression:
[tex]\displaystyle\frac{7}{9} \div \frac{4}{9} = a\frac{b}{c}[/tex]
The solving of the above expression can be done in the following manner:
[tex]\displaystyle\frac{7}{9} \div \frac{4}{9}\\\\\frac{7}{9}\times \frac{9}{4}\\\\\frac{7}{4} =\frac{(4\times 1) + 3}{4}= 1\frac{3}{4}[/tex]
Comparing the right side of the expression, we have,
[tex]a\displaystyle\frac{b}{c} = 1\frac{3}{4}[/tex]
Comparing, we get,
a = 1, b = 3, c = 4
Option B) s the correct option.
Match the subtraction expressions with their answers.
Answer:
the order is
2,4,1,3
(the 1st answer is the 2nd option)
Answer:
1. (a² - b)/(a³b²)= 1/ab² - 1/a²b
2. (b - a)/a³b³ = 1/a³b² - 1/a²b³
3. (2 - ab²)/(a²b³) = 2/a²b³ - 1/ab
4. (2 - a)/a³b³ = 2/a³b³ - 1/a²b³
Step-by-step explanation:
To do this we'll break down fraction to least term through division.
The solution is as follows
1. (a² - b)/(a³b²)
Splitting the fraction;
a²/a³b² - b/a³b²
= 1/ab² - 1/a²b
2. (b - a)/a³b³
Splitting the fraction.
b/a³b³ - a/a³b³
1/a³b² - 1/a²b³
3. (2 - ab²)/(a²b³)
Splitting the fraction.
2/a²b³ - ab²/a²b³
2/a²b³ - 1/ab
4. (2 - a)/a³b³
Splitting the fraction
2/a³b³ - a/a³b³
2/a³b³ - 1/a²b³
Do you guys know the answer for number 4
Answer:
90
Step-by-step explanation:
90-20%=72
72-20-52
plus everything else doesnt match up and with taxes involved so the oroginal price was 90
Urgent help needed
Solve for x. Show your work.
Answer:
First exercise: [tex]x=7[/tex]
Second exercise: [tex]x=2[/tex]
Step-by-step explanation:
According to the Intersecting Secants Theorem the products of the segments of two secants that intersect each other outside a circle, are equal.
Knowing this, in order to solve the first exercise and the second exercise, we can write the following expressions and solve for "x":
For the first exercise, we get:
[tex](5)(5+x)=6(6+4)\\\\25+5x=60\\\\5x=60-25\\\\x=\frac{35}{5}\\\\x=7[/tex]
For the second exercise, we get:
[tex](4)(4+x)=3(3+5)\\\\16+4x=24\\\\4x=24-16\\\\x=\frac{8}{4}\\\\x=2[/tex]
If P is parentheses and M is Multiplication and S is subtraction, what is EDA In PEMDAS? Very confused!
E is exponents, D is division, A is addition
Answer:
E- exponent D- division A- addition
Step-by-step explanation:
PEMDAS is an acronym which means
P- parenthesis
E- exponents
M- multiplication
D- division
A- addition
S- subtraction
used for two or more operation in a single expression, the order of letters in the PEMDAS tells us what to calculate first, second, third and so on, until the calculation is complete.
A man earns #6000 every month, he spends 1/5 of his salary on children's education and 5/8 on his aged mother and unemployed sister. How much does he have left?
Answer:
$1050
Step-by-step explanation:
To solve, multiply your two expenses against your $6000 and find the difference.
The man spends 1/5 of his salary on children's education.
To find how much he spends on his children's education in dollars, multiply 1/5 against $6000.
[tex]\frac{1}{5} *6000\\1200[/tex]
The man spends $1200 on children's education.
The man spends 5/8 of his salary on his aged mother and unemployed sister.
Repeat the same process as the first step, this time multiplying 5/8 against $6000.
[tex]\frac{5}{8} *6000\\3750[/tex]
The man spends $3750 on his aged mother and unemployed sister.
Add these two expenses together.
[tex]1200+3750\\4950[/tex]
The man has combined expenses of $4950.
To find how much money he has left, subtract his expenses from his $6000 income.
[tex]6000-4950\\1050[/tex]
The man has $1050 remaining.
If p —> q and q —> r are true conditional statements,
then p —> r is a true conditional statement.
This is the Law of Detachment.
True or False
Answer:
False; this is the law of syllogism.
Step-by-step explanation:
Law of Detachment is:
1) p->q
2) p
------------------------
Conclusion: q
Law of syllogism is:
1) p->q
2) q->r
---------------------
Conclusion: p->r
Find the equation, in standard form, of the line passing through the points (2,-3) and (4,2).
Answer:
5x - 2y = -4Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
Te formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
===========================================
We have two points: (2, -3) and (4, 2). Substitute:
[tex]m=\dfrac{2-(-3)}{4-2}=\dfrac{5}{2}[/tex]
[tex]y-(-3)=\dfrac{5}{2}(x-2)\\\\y+3=\dfrac{5}{2}(x-2)[/tex]
Convert it to the standard form [tex]Ax+By=C[/tex]:
[tex]y+3=\dfrac{5}{2}(x-2)[/tex] multiply both sides by 2
[tex]2y+6=5(x+2)[/tex] use the coordinates of the point
[tex]2y+6=5x+10[/tex] subtract 6 from both sides
[tex]2y=5x+4[/tex] subtract 5x from both sides
[tex]-5x+2y=4[/tex] change the signs
[tex]5x-2y=-4[/tex]
What is the x-coordinate of the vertex of the parabola whose equation is y = 3x^2 + 12x + 5?
Answer:
(-2,-7)
Step-by-step explanation:
Answer:
x= -2
Step-by-step explanation:
-b/2a = x
-(12)/2(2) = x
-12/6 = x
-2 = x
Find the equation for the linear function that passes through the points (−5,−4) and (5,2). Answers must use whole numbers and/or fractions, not decimals.
Use the line tool below to plot the two points.
State the slope between the points as a reduced fraction.
State the y-intercept of the linear function.
State the linear function
The equation of the line is y = 0.6*x - 1, the graph is in the image at the end.
How to find the linear equation?
A linear equation in the slope-intercept form can be written as:
y = ax + b
Where a is the slope and b is the y-intercept.
If a line passes through two points (x₁, y₁) and (x₂, y₂), then the slope is given by:
a = (y₂ - y₁)/(x₂ - x₁)
Here we have the points (−5,−4) and (5,2), so the slope is:
a = (2 + 4)/(5 + 5) = 6/10 = 0.6
y = 0.6*x + b
And it passes through (5, 2), then:
2 = 0.6*5 + b
2 - 0.6*5 = b
-1 = b
The equation is:
y = 0.6*x - 1
The graph is in the image below.
What is the value of x in the equation 1/2x-3/4=3/8-5/8
Answer:
x=1
Step-by-step explanation:
1/2x-3/4=3/8-5/8
Combine like terms on the right hand side
1/2x-3/4=-2/8
Simplify the fraction
1/2x-3/4=-1/4
Add 3/4 to each side
1/2x-3/4+3/4 = -1/4+3/4
1/2x = 2/4
Multiply each side by 2
1/2x *2 = 2/4*2
x = 4/4
x=1
Answer:
the answer its 1
Step-by-step explanation:
When it is 6:00 a.m. in Honolulu, it is 3:00 p.m. in London. Just before Paul’s flight from Honolulu to London, he called his friend Nigel, who lives in London, asking what kind of clothing to bring. Nigel explained that London was in the middle of some truly peculiar weather. The temperature was currently 30°C, and was dropping steadily at a rate of 1°C per hour. Paul’s flight left Honolulu at 2:00 p.m. Thursday, Honolulu time, and got into London at 12:00 p.m. Friday, London time. What kind of clothing would have been appropriate for Paul to be wearing when he got off the plane? a. shorts and sandals, appropriate for around 90-105°F b. winter wear, appropriate for around 20-45°F c. street clothes, appropriate for around 70-85°F d. a light jacket, appropriate for around 50-65°F
Answer:
b. winter wear, appropriate for around 20-45°F c.
Step-by-step explanation:
Answer:
b. winter wear, appropriate for around 20-45°F
Step-by-step explanation:
When it is 6:00 hours in Honolulu, it is 15:00 hours in London, this means that there are 15 - 6 = 9 hours of difference.
Paul got into London at 12:00 p.m, that is, at 12 - 9 = 3:00 p.m. Friday Honolulu time. Paul’s flight left Honolulu at 2:00 p.m. Thursday, so he spent 25 hours flighting.
When the flight started, the temperature in London was 30 °C, after 25 hours the temperature dropped 25 °C, so it was 30 - 25 = 5 °C.
To convert from °C to °F, we use the following formula:
(x °C × 9/5) + 32 = y °F
Replacing with x = 5
(5 °C × 9/5) + 32 = 41 °F
help me i need this please
Answer:
B.
Step-by-step explanation:
P(something not happening)+P(something happening)=1 or 100%.
So if we have
P(something not happening)+40%=100%
Then the P(something not happening)=60% since 60%+40%=100%.
Yes I was using the event="something not happening" as the complement of something happening.
In fancy notation, some people might write:
[tex]P(A)+P(A')=1[/tex]
or
[tex]P(A)+P(A^c)=1[/tex]
angle a measures 110 degrees angle b measures 72 degrees the measure of angle D is
Answer:
Angle D is 70, I believe
Angle D would be supplementary to A
Witch inequality represents the sentence below two or more than a number is less than 14 HELPPPPPPPP
Answer:
its the second choice 2 + n< 14
The lengths of two sides of a right triangle are 12 inches and 15 inches. What is the difference between the two possible lengths of the third side of the triangle? Round your answer to the nearest tenth. 10.2 inches 24.0 inches 28.2 inches 30.0 inches
Answer:
10.2 inches
Step-by-step explanation:
we know that
In this problem we have two cases
First case
The given lengths are two legs of the right triangle
so
[tex]a=12\ in, b=15\ in[/tex]
Applying the Pythagoras Theorem
Find the length of the hypotenuse
[tex]c^{2}=a^{2} +b^{2}[/tex]
substitute
[tex]c^{2}=12^{2} +15^{2}[/tex]
[tex]c^{2}=369[/tex]
[tex]c=19.2\ in[/tex]
Second case
The given lengths are one leg and the hypotenuse
so
[tex]a=12\ in, c=15\ in[/tex]
Applying the Pythagoras Theorem
Find the length of the other leg
[tex]b^{2}=c^{2} - a^{2}[/tex]
substitute
[tex]b^{2}=15^{2} - 12^{2}[/tex]
[tex]b^{2}=81[/tex]
[tex]b=9\ in[/tex]
Find the difference between the two possible lengths of the third side of the triangle
so
[tex]19.2-9=10.2\ in[/tex]
Answer:
10.2
Step-by-step explanation:
is a pimp ting
Write the point slope form of the equation of the line through the given point with the given slope. Show your work!
12) through (4,-4) , slope =-2
Answer:
y+4=-2(x-4)
Simplified- y=-2x+4
Step-by-step explanation:
y+4= -2(x-4)
y+4= -2x+8
-4. -4
y=-2x+4
Given: The coordinates of triangle PQR are P(0, 0), Q(2a, 0), and R(2b, 2c).
Prove: The line containing the midpoints of two sides of a triangle is parallel to the third side.
As part of the proof, find the midpoint of PR
Answer:
The line containing the midpoints of two sides of a triangle is parallel to the third side ⇒ proved down
Step-by-step explanation:
* Lets revise the rules of the midpoint and the slope to prove the
problem
- The slope of a line whose endpoints are (x1 , y1) and (x2 , y2) is
[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
- The mid-point of a line whose endpoints are (x1 , y1) and (x2 , y2) is
[tex](\frac{x_{1}+x_{2}}{2},\frac{y_{1}+y_{2}}{2})[/tex]
* Lets solve the problem
- PQR is a triangle of vertices P (0 , 0) , Q (2a , 0) , R (2b , 2c)
- Lets find the mid-poits of PQ called A
∵ Point P is (x1 , y1) and point Q is (x2 , y2)
∴ x1 = 0 , x2 = 2a and y1 = 0 , y2 = 0
∵ A is the mid-point of PQ
∴ [tex]A=(\frac{0+2a}{2},\frac{0+0}{2})=(\frac{2a}{2},\frac{0}{2})=(a,0)[/tex]
- Lets find the mid-poits of PR which called B
∵ Point P is (x1 , y1) and point R is (x2 , y2)
∴ x1 = 0 , x2 = 2b and y1 = 0 , y2 = 2c
∵ B is the mid-point of PR
∴ [tex]B=(\frac{0+2b}{2},\frac{0+2c}{2})=(\frac{2b}{2},\frac{2c}{2})=(b,c)[/tex]
- The parallel line have equal slopes, so lets find the slopes of AB and
QR to prove that they have same slopes then they are parallel
# Slope of AB
∵ Point A is (x1 , y1) and point B is (x2 , y2)
∵ Point A = (a , 0) and point B = (b , c)
∴ x1 = a , x2 = b and y1 = 0 and y2 = c
∴ The slope of AB is [tex]m=\frac{c-0}{b-a}=\frac{c}{b-a}[/tex]
# Slope of QR
∵ Point Q is (x1 , y1) and point R is (x2 , y2)
∵ Point Q = (2a , 0) and point R = (2b , 2c)
∴ x1 = 2a , x2 = 2b and y1 = 0 and y2 = 2c
∴ The slope of AB is [tex]m=\frac{2c-0}{2b-2a}=\frac{2c}{2(b-c)}=\frac{c}{b-a}[/tex]
∵ The slopes of AB and QR are equal
∴ AB // QR
∵ AB is the line containing the midpoints of PQ and PR of Δ PQR
∵ QR is the third side of the triangle
∴ The line containing the midpoints of two sides of a triangle is parallel
to the third side
Answer:
b,c
Step-by-step explanation:
That guy above took so long
cos155° = _____ -cos25° cos 55° cos(-25)°
Answer:
- cos 25°
Step-by-step explanation:
Cosine function is one of the trigonometric functions. Cosine function is regarded as an even function, which means that f(-x) = f(x). Also, cosine function is positive in the first quadrant and the last quadrant and negative in the second quadrant and the third quadrant. 155° lies in the second quadrant since 155° is smaller than 180°. Therefore, the basic angle or the reference angle of 155° is 180° - 155° = 25°. We know that cos 155° will be negative because it lies in the second quadrant and cos 25° will be positive because it lies in the first quadrant. Since cos 55° is positive, and cos (-25°) = cos 25° by the even function property, therefore option 2 and option 3 are incorrect since cos 155° is negative. Therefore, option 1 is the correct answer i.e. cos 155° = - cos 25°!!!
Answer:
- [tex]cos25^{o}[/tex]
Step-by-step explanation:
Hope This Helps!!!
A.obtuse
B.straight
C.acute
D.right
A. obtuse. The angle R is obtuse.
An obtuse angle is an angle greater than 90° and less than 180°. So, in the image attached we can see that the angle R is greater than 90° and less than 180°.
1.) Harold’s truck has broken down and needs some repairs. The hourly pay for labor is $35 per hour, and the cost of the parts is $90. The mechanic’s estimate is $265. How many hours does the mechanic expect to need to fix the truck?
Answer:
5 hours
Step-by-step explanation:
The total amount of the repair is $265 and includes parts and an hourly rate. We are told the parts are $90. Subtract the price of the parts, $90, from the total of $265.
$265 - $90 = $175
The $175 is only due to the hourly rate.
Now we divide the total due to the hours by the hourly rate to find the number of hours.
175/35 = 5
Answer: 5 hours
The rule as a mapping for the translation of a rectangle is (x, y) → (x – 2, y + 7). Which describes this translation?
Answer:
The translation is 2 units at left and 7 units up
Step-by-step explanation:
we have that
The rule of the translation is
(x, y) → (x – 2, y + 7)
That means----> The translation is 2 units at left and 7 units up
Answer:
2 units at left and 7 units up
Step-by-step explanation:
If the rule as a mapping for the translation of a rectangle is (x, y) → (x – 2, y + 7), 2 units at left and 7 units up describes this translation.
Suppose you multiplied the cereal box dimensions in a different order:
V = (x)(4x+3)(4x)
First, (X)(4x+3) =
DONE
[tex]\bf V=(x)(4x+3)(4x)\implies \cfrac{V}{4x}=(x)(4x+3)[/tex]
Answer:
[tex]V=(x)(4x+3)(4x)=16x^2+12x[/tex]
Step-by-step explanation:
Given : Expression [tex]V = (x)(4x+3)(4x)[/tex]
To find : Suppose you multiplied the cereal box dimensions in a different order ?
Solution :
The given expression is the product of three numbers,
[tex]V = (x)(4x+3)(4x)[/tex]
First we multiply first two terms,
[tex](x)(4x+3)=4x^2+3x[/tex]
Substitute back,
[tex]V = (4x^2+3x)(4x)[/tex]
Then multiply the left terms,
[tex]V =16x^2+12x[/tex]
Therefore, [tex]V=(x)(4x+3)(4x)=16x^2+12x[/tex]
What is the center of the circle shown below?
Answer:
A. S
Step-by-step explanation:
The edge of the circle would be M and there is a line to the center showing the radius. The second letter shows the center.
point S is the centre of the given circle.
Determining the centre of a circle.You need to know some details about a circle, such as its equation or certain locations on the circle, in order to locate its center.
Drawing the perpendicular bisectors of each chord will allow you to determine the circle's center if you are aware of the location where two perpendicular chords connect. The center of the circle is where the perpendicular bisectors intersect.
Therefore, based on the given figure, the centre is the point S.
Learn more on centre of a circle here: https://brainly.com/question/29458405
#SPJ2
find the midpoint between -7+4i and 3-2i
Answer:
-2 + i
Step-by-step explanation:
The midpoint is the average:
[ (-7 + 4i) + (3 − 2i) ] / 2
Combine like terms:
(-4 + 2i) / 2
Divide:
-2 + i
Find the coordinates of P so that P partitions the segment AB in the ratio 1:1 if
A(13,1) and B(−5,−3)?
.
Answer:
P(4, - 1 )
Step-by-step explanation:
The ratio 1 : 1 represents the midpoint of segment AB
Using the midpoint formula
[ 0.5(x₁ + x₂ ), 0.5(y₁ + y₂ ) ]
with (x₁, y₁ ) = (13, 1) and (x₂, y₂ ) = (- 5, - 3), so
P = [0.5(13 - 5), 0.5(1 - 3) ] = [0.5(8), 0.5(- 2) ] = (4, - 1 )
the midpoint P has the coordinates (4, −1).
To find the coordinates of point P that partitions segment AB in a 1:1 ratio, also known as the midpoint, we use the midpoint formula. Given the coordinates A(13,1) and B(−5,−3), the midpoint formula is ((x1 + x2)/2, (y1 + y2)/2).
Applying the values from A and B:
For x-coordinate: (13 − 5) / 2 = 8 / 2 = 4For y-coordinate: (1 − 3) / 2 = −2 / 2 = −1Therefore, the midpoint P has the coordinates (4, −1).